2002
DOI: 10.1074/jbc.m201586200
|View full text |Cite
|
Sign up to set email alerts
|

Basic Residues in Azurocidin/HBP Contribute to Both Heparin Binding and Antimicrobial Activity

Abstract: Azurocidin/CAP37/HBP is an antimicrobial and chemotactic protein that is part of the innate defenses of human neutrophils. In addition, azurocidin is an inactive serine protease homolog with binding sites for diverse ligands including heparin and the bovine pancreatic trypsin inhibitor (BPTI). The structure of the protein reveals a highly cationic domain concentrated on one side of the molecule and responsible for its strong polarity. To investigate the role of this highly basic region, we produced three recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Three of these, the 'diverged serine proteases' (Y12274 and Y12286) and the EU325556 inactive lipase (very similar to EF600061), are abundant in the lumen of the gut (Pauchet et al, 2008). A possible role in innate immunity is suggested by parallels with vertebrates in which 'serprocidins' have synergistic anti-microbial activity with active enzymes (McCabe et al, 2002), possibly by the generation of shorter microbiocidal peptides (Tsuji et al, 2001). Alternatively, at least one inactive hydrolase retains the ability to bind a member of the Kunitz serine proteinase inhibitor family (Petersen et al, 1993) so perhaps the inactive hydrolases can act as a sink for diet-derived inhibitors (Prabhakar et al, 2007) or are part of a putative sensing system for inhibitors (Bown et al, 2004).…”
Section: Hydrolasesmentioning
confidence: 97%
“…Three of these, the 'diverged serine proteases' (Y12274 and Y12286) and the EU325556 inactive lipase (very similar to EF600061), are abundant in the lumen of the gut (Pauchet et al, 2008). A possible role in innate immunity is suggested by parallels with vertebrates in which 'serprocidins' have synergistic anti-microbial activity with active enzymes (McCabe et al, 2002), possibly by the generation of shorter microbiocidal peptides (Tsuji et al, 2001). Alternatively, at least one inactive hydrolase retains the ability to bind a member of the Kunitz serine proteinase inhibitor family (Petersen et al, 1993) so perhaps the inactive hydrolases can act as a sink for diet-derived inhibitors (Prabhakar et al, 2007) or are part of a putative sensing system for inhibitors (Bown et al, 2004).…”
Section: Hydrolasesmentioning
confidence: 97%
“…73,74 A highly cationic domain concentrated on one side of the molecule was identified as crucial for antimicrobial activity. 75 In another study, a synthetic peptide based on amino acid residues 20 to 44 was shown to retain antimicrobial activity, and it was proposed that its maximal activity requires the presence of a free sulfhydryl group. 76 Peptides derived from the same domain are also active against adenovirus and herpes simplex virus type I (HSV-1).…”
mentioning
confidence: 99%
“…sporozoites were stained (Feng et al 2006). The dye binds to aminomoieties (McCabe et al 2002) and therefore should predominantly react with basic proteins, particularly to those with many moieties, e. g. histones, hyaluronates, glycosaminglycans or amino sugars (Suniara et al 2000;Spadaro et al 2007). However, recent proteomic studies on refractile bodies of E. tenella (de Venevelles et al 2006) rather suggest a predominance of acidic proteins than basic ones and to our knowledge other studies on the composition of refractile bodies are not available.…”
Section: Discussionmentioning
confidence: 99%
“…As another option, membrane-permeant reactive tracers, such as 5(6)-carboxyfluorescein diacetate succinimidyl ester (CFSE) seemed promising. CFSE is intracellularly converted into a green-fluorescent molecule by esterases and binds covalently to amino groups (McCabe et al 2002;Spadaro et al 2007). This staining was recently shown to be useful for tracing Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%